Chern-Simons induced thermal friction on axion domain walls - Saquib Hassan; Gaurang Ramakant Kane; John March-Russell; Georges Obied (Journal of High Energy Physics)
Abstract We study the dynamics and interactions of the solitonic domain walls that occur in realistic axion electrodynamics models including the Chern-Simons interaction, aϵ μνλσ F μν F λσ , between an axion a(x) of mass m a , and a massless U(1) gauge field, e.g. EM, interacting with strength α = e 2/4π with charged matter, e.g. electron-positron pairs. In particular, in the presence of a U(1) gauge-and-matter relativistic thermal plasma we study the friction experienced by the walls due to the Chern-Simons term. Utilizing the linear response method we include the collective effects of the plasma, as opposed to purely particle scattering across the wall (as is done in previous treatments) which is valid only in the thin wall regime that is rarely applicable in realistic cases. We show that the friction depends on the Lorentz-γ-factor-dependent inverse thickness of the wall in the plasma frame, ℓ −1 ~ γm a , compared to the three different plasma scales, the temperature T, the Debye mass m D ~ α T $$ \sqrt{α }T $$ , and the damping rate Γ ~ α 2 T, and elucidate the underlying physical intuition for this behavior. (For friction in the thin-wall-limit we correct previous expressions in the literature.) We further consider the effects of long-range coherent magnetic fields that are possibly present in the early universe and compare their effect with that of thermal magnetic fields. We comment on the changes to our results that likely apply in the thermal deconfined phase of a non-Abelian gauge theory. Finally, we briefly discuss the possible early universe consequences of our results for domain wall motion and network decay, stochastic gravitational wave production from domain wall networks, and possible primordial black hole production from domain wall collapse, though a more complete discussion of these topics is reserved for a companion paper.